Possibility of Using Back-Pressure Turbine in the Iraqi Petroleum Industry (Journal of Engineering, 2011)
Dura refinery, Baghdad, utilizes at the same time two forms of energy: electricity and heat. Nowadays, these two forms of energy are supplied by a bottoming cogeneration plant. The present paper describes this cogeneration system in detail. Meanwhile, the theoretical analysis was conducted according to the 1st and 2nd laws of thermodynamics to evaluate system performance. Based on the results of such analysis and considering the advantages of back-pressure turbine properties, two alternative plants based on a true cogeneration system have been designed and analyzed. The results showed a substantial increase in efficiency (6–13%) as well as the achievement of (24%) saving in fuel consumption. Moreover, the findings of the present work indicate that these alternative plants can produce more electricity than is required by the refinery. Such excess power can be effectively sold to the main electric network, improving overall energy utilization